SULUK DAN PERUBAHAN PERILAKU SOSIAL SALIK (TELAAH TEORI KONSTRUKSI SOSIAL PETER L BERGER DAN THOMAS LUCKMAN) - Asmanidar Asmanidar (Abrahamic Religions: Jurnal Studi Agama-Agama, 2021)
Social change after following suluk is a result that must be achieved by the salik. The change in question is a change in attitude for the better in everyday life after following suluk. This article also aims to find out how to internalize the value of suluk on salik in life and social changes in society, and in this case it is reviewed from one of the theories put forward by Peter Berger. by referring to three aspects, namely externalization, objectification and internalization. This article is a study using qualitative and descriptive approaches, in which informants are obtained by using purposive sampling method. To analyze this paper, the author certainly still uses a social construction theory in which changes in society do not happen by themselves but there are certain patterns that encourage and influence them. Based on the results of what the author has done, both in the form of initial assessments and also interviews with several salik, namely to achieve internalization of the values of suluk in salik who have participated in suluk both in Lueng Ie dayah and Tgk, Zulfan, must have an objectivation externalization stage. only then at the internalization stage. In salik who have participated in suluk, not all of them are able to absorb the values that are applied to suluk worship activities significantly, this is due to the influence of interaction patterns and the process of assimilation with the outside environment that is still happening, so that these values have not been applied comprehensively in the form of changes. attitudes and behavior in social life, and this is of course not as easy as turning the palm of the hand. The salik must strive with all their might so that the very high values of suluk worship can be slowly applied in life in the hope of becoming an example for themselves and their environment.